ASSESSING THE VIABILITY AND PROPERTIES OF DENTAL PULP STEM CELLS FROM HUMAN THIRD MOLARS FOR POTENTIAL REGENERATIVE ENDODONTICS APPLICATIONS - Bander Hajji Almutairi, Hessa Faisal Saad Alsulaiman, Faisal Mohammed Alkhayrat, Turki Mohammed Matar Almutairi, Omar Mohammed Mohammed Alasimi, Naif Matar Almutairi (Chelonian Research Foundation, 2022)
Dental pulp stem cells (DPSCs) isolated from extracted teeth present an exciting stem cell source for potential applications in regenerative endodontics to restore damaged or diseased pulp tissue. However, the long-term viability and properties of DPSCs obtained from different tooth sources over extended culture periods remain incompletely characterized. This study aimed to address this research gap by isolating and culturing stem cells from human third molar dental pulp over six passages. Cell viability, morphology, proliferation, expression of mesenchymal stem cell surface markers, and differentiation capacity into odontoblasts and adipocytes were analyzed at each passage. DPSCs extracted from 15 impacted third molars from patients age 18-25 years were cultured and monitored over six serial passages. Cell viability remained excellent through passage 6 with 98% viability. Spindle-shaped fibroblastic morphology was maintained consistently. Doubling time averaged between 30-36 hours across passages. Immunophenotyping revealed positive expression of mesenchymal stem cell surface markers CD73, CD90, and CD105 that was sustained consistently through the final passage. Multilineage differentiation capacity into both osteogenic and adipogenic lineages was demonstrated. Results indicate DPSCs derived from human third molars represent a viable and stable stem cell population for investigation in regenerative endodontics approaches to restore damaged dental pulp tissue and whole tooth structures. Findings support their further study in 3D scaffold cultures and in vivo transplantation models.